Thiosulfonylation of alkenes with the insertion of sulfur dioxide under non-metallic conditions. Issue 20 (12th September 2018) - He, Fu-Sheng; Wu, Youqian; Zhang, Jun; Xia, Hongguang; Wu, Jie
Abstract : A three-component reaction of 1-(2-allylaryl)thioureas, sulfur dioxide, and aryldiazonium tetrafluoroborates under mild conditions is realized, leading to sulfonated [3, 1]-benzothiazepines in good yields. High efficiency is observed for this non-metallic transformation. Abstract : A three-component reaction of 1-(2-allylaryl)thioureas, sulfur dioxide, and aryldiazonium tetrafluoroborates under mild conditions is realized, leading to sulfonated [3, 1]-benzothiazepines in good yields. The reaction proceeds smoothly at room temperature in the absence of any catalysts or additives. A high efficiency is observed for this non-metallic transformation. Preliminary mechanistic investigation shows that a radical process is involved. This protocol represents an efficient and attractive strategy for the preparation of seven-membered heterocyclic compounds containing a sulfonyl group.